2015
DOI: 10.3109/17453674.2015.1071111
|View full text |Cite
|
Sign up to set email alerts
|

Training effect of a virtual reality haptics-enabled dynamic hip screw simulator

Abstract: Background and purpose — Virtual reality (VR) simulation offers a safe, controlled, and effective environment to complement training but requires extensive validation before it can be implemented within the curriculum. The main objective was to assess whether VR dynamic hip screw (DHS) simulation has a training effect to improve objective performance metrics.Patients and methods — 52 surgical trainees who were naïve to DHS procedures were randomized to 2 groups: the training group, which had 5 attempts, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…A number of studies have investigated the improvement in trainee performance on a VR simulator over the course of a training session, or sessions, demonstrating progression along a learning curve (Table III). 26,[36][37][38][39][40][41][42] Pollard et al 38 demonstrated this learning curve for simulated hip arthroscopy with the patient in both lateral and supine positions, measuring time taken, the total path-length of the hands and the number of hand movements, for 20 orthopaedic trainees with minimal hip arthroscopy experience. A similar learning curve was demonstrated using the Sheffield Knee Arthroscopy Training System (University of Sheffield, Sheffield, UK) in both experienced and inexperienced individuals, and a passive haptic knee arthroscopy simulator in medical students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have investigated the improvement in trainee performance on a VR simulator over the course of a training session, or sessions, demonstrating progression along a learning curve (Table III). 26,[36][37][38][39][40][41][42] Pollard et al 38 demonstrated this learning curve for simulated hip arthroscopy with the patient in both lateral and supine positions, measuring time taken, the total path-length of the hands and the number of hand movements, for 20 orthopaedic trainees with minimal hip arthroscopy experience. A similar learning curve was demonstrated using the Sheffield Knee Arthroscopy Training System (University of Sheffield, Sheffield, UK) in both experienced and inexperienced individuals, and a passive haptic knee arthroscopy simulator in medical students.…”
Section: Resultsmentioning
confidence: 99%
“…The insightMIST (3D Systems, Rock Hill, South Carolina) shoulder VR simulator has also been shown to provide learner progression, supporting VR simulation in shoulder surgical training. 37 Two studies conducted by Sugand et al 40,42 have explored the training effect of both the TouchSurgery application (TouchSurgery Labs, London, United Kingdom) and the TraumaVision Dynamic Hip Screw VR (Swemac, Linköping, Sweden) simulator (3D Systems, Rock Hill, South Carolina), showing progression by medical students and surgical trainees respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation is a well-recognised teaching adjunct to train high-risk tasks within a safe and controlled environment to prevent harm to patients (15)(16)(17)(18)(19)(20). Simulation in orthopaedic surgery can be divided into three broad categories: 1) low-fidelity saw bones (dry-lab) 2) virtual reality (VR) and 3) cadaveric (wet-lab) simulation (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation enables surgeons to acquire skill outside of the OR and allows them to practice in a low-pressure situation, providing them with time to think through the process and reflect on their surgical technique [7]. Simulation is also thought to improve a surgeon's accuracy, which is important when aiming for a low TAD and a minimal number of wire insertions all while avoiding drilling the wire into the joint space [17][18][19].…”
Section: Introductionmentioning
confidence: 99%